(3ebOeI aj GdUMGaI GdEaQjbjIs - (3YHO GdQMef, YhGWas ((3GdbGgQI (B:s (3OGQ GdacQ GdYQHj,s, 1985)
(3GdNUGFU GdeejRI ddhGbY GdEaQjbj aj GdeQMdI GdQGgfI(B.s
Keywords: (3GdUMGaIs -- (3EaQjbjGs -- (3JGQjNs